Pengembangan Media Pembelajaran Kesehatan Reproduksi Remaja pada Remaja Awal di SMPN 19 Kota Jambi - Pauline Kusmaryati; Netti Herawati; Ajeng Galuh Wuryandari (Universitas Baiturrahim, 2022)
Various studies have shown that adolescents have very complex problems along with the transitional period experienced by adolescence, a problem that stands out among adolescents, namely the problems surrounding TRIAD KRR (sexuality, HIV and AIDS as well as drugs). The role of the media is important in shaping the knowledge of adolescents in understanding reproductive health problems. Multimedia is a combination of media which is more than two media consisting of integrated text, graphics, images, photos, audio, video and animation. This study uses research and development (R and D) methods. The population in this study were students at SMPN 19 Jambi City. The sample was selected using purposive sampling technique totaling 35 students. This research was conducted from March to November 2020. The data analysis in this study used qualitative analysis techniques and quantitative descriptive. Quantitative data collection was carried out by measuring the level of students' initial knowledge (pre-test), then introducing a 10-minute video media for adolescent reproductive healt. Evaluation is carried out by measuring the level of knowledge (post test) and evaluating student responses to the experience of accessing the developed video. Overall the percentage level of media feasibility by material experts is 98.6% with the very feasible category. The results of eligibility by media experts obtained a percentage level of 80% with the feasible category.The results of the Wilcoxon test showed a significant difference (r-value 0,000) from the students' knowledge before and after the intervention was given. The results of the percentage of respondents' responses to the media are 93% with a very good. For further research, it is hoped that this video media can be developed with a more specific topic regarding adolescent reproductive health while still paying attention to the duration of the video and can also be developed learning media with interactive multimedia.